An Intertextual Analysis of “Menombak Matahari”, “Sarpakuda”, and Babad Mangir Suradipura - Faqih Sulthan; Testiana Deni Wiajayatiningsih (Surakarta English and Literature Journal, 2024)
The creation of a new text is highly influenced by previous texts, known as intertextual relationships. For instance, the short stories "Menombak Matahari" and "Sarpakuda" portray the resistance of Ki Ageng Mangir and the agony of Putri Pambayun, and are likely inspired by preexisting texts. This research examines the intertextual relationship between these two short stories and Babad Mangir from Suradipura, an old literature, as modern literary works. A comparative and an intertextual approach have been used to achieve this goal. By comparing the textual data of the short stories and the text of Babad Mangir Suradipura, it is evident that both short stories use Babad Mangir as a source of inspiration but develop their conflicts differently while still using traditional themes.